Love Monster and the perfect present - Bright, Rachel (New York : Farrar, Straus Giroux, 2014)
Love Monster is determined to give his best friend, a lovely girl monster, the perfect present on Gift Day, so when he discovers he cannot afford to buy anything special enough, he has an idea to make something, instead.
Keywords: Gifts -- Fiction; Creative ability -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Monsters -- Fiction; JUVENILE FICTION / Social Issues / Emotions & Feelings; JUVENILE FICTION / Humorous Stories